Development of 4C-Integrated Karthon (Kartu Pacelathon) as an Innovative Learning Media for Javanese Dialogue - Dewi, Saraswati Murtyas; Insani, Nur Hanifah (AL-ISHLAH: Jurnal Pendidikan, 2024)
The proficiency of seventh-grade students at SMPN 2 Semarang in writing and reciting Javanese dialogue remains relatively low, highlighting the need for effective learning media. Mastery of this skill is a fundamental objective of Javanese language education, aimed at fostering good manners among students. This study seeks to 1) assess the needs of both teachers and students for the development of karthon-based learning media, and 2) design and validate a prototype of such media tailored for teaching Javanese dialogue to seventh-grade students at SMPN 2 Semarang. The research employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as conceptualized by Reiser and Mollenda. Data collection methods included interviews and questionnaires, while both qualitative and quantitative techniques were utilized for data analysis. The study involved 288 seventh-grade students at SMPN 2 Semarang during the 2021/2022 academic year, with a randomly selected sample of 37 students. The research revealed a substantial demand for card-based learning media among the students. The developed prototype, featuring writing and reading cards, underwent expert review and field testing, demonstrating high suitability for classroom implementation. The findings of this study offer a valuable solution for teachers aiming to enhance Javanese dialogue skills in seventh-grade students at SMPN 2 Semarang, integrating the 4C skills—critical thinking, communication, collaboration, and creativity—into the learning process.